2022
DOI: 10.13057/biodiv/d231113
|View full text |Cite
|
Sign up to set email alerts
|

Determinant of farmers’ participation and biodiversity status in the program of agroforestry rehabilitation in Sudan

Abstract: Abstract. Hemida M, Mulyana B, Vityi A. 2022. Determinant of farmers’ participation and biodiversity status in the program of agroforestry rehabilitation in Sudan. Biodiversitas 23: 5638-5645. The agroforestry Rehabilitation Program (ARP) was launched in Nabag Reserve Forest (NRF), Sudan, to rehabilitate the forest cover and improve livelihoods for communities around the forest. To enhance the efficacy of such rehabilitation programs, it is crucial to understand the impact of various factors on community perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…Additionally, frequent civil wars have resulted in significant losses of vegetation cover [42]. A study by [1,2,38,43] corroborates these findings, suggesting deforestation, flooding, soil erosion, and unplanned urban and agricultural expansion could lead to such LULC changes. The study also emphasizes that LULC modifications, influenced by varying environmental, political, demographic, and socio-economic conditions, are dynamic and directly affect communities living near forests.…”
Section: Assessment Of Land Use/land Cover Changementioning
confidence: 89%
See 1 more Smart Citation
“…Additionally, frequent civil wars have resulted in significant losses of vegetation cover [42]. A study by [1,2,38,43] corroborates these findings, suggesting deforestation, flooding, soil erosion, and unplanned urban and agricultural expansion could lead to such LULC changes. The study also emphasizes that LULC modifications, influenced by varying environmental, political, demographic, and socio-economic conditions, are dynamic and directly affect communities living near forests.…”
Section: Assessment Of Land Use/land Cover Changementioning
confidence: 89%
“…Studies on forest rehabilitation indicate that tree planting typically accelerates the recovery of forest vegetation [37]. Hemida et al [38] that the increase in forest cover during a certain period can be attributed to the Taungya agroforestry program initiated by the FNC in early 2005 and continuing to the present day. Salih [39] also reported that the Taungya program positively contributed to rehabilitating 3024 ha of NFR between 2005 and 2013.…”
Section: Assessment Of Land Use/land Cover Changementioning
confidence: 99%
“…This gender disparity can be attributed to a multitude of factors; deeply entrenched social norms are among the main ones. As explained above, these norms contribute to women's lower wealth levels and restricted access to land, labour and extension services, as well as limitations imposed by inheritance systems, and the lack of rights for women to grow trees (Kiptot and Franzel 2011;Bourne et al 2015;Diawuo et al 2019;Hemida et al 2022).…”
Section: Women As Agents Of Changementioning
confidence: 99%
“…Thus: agrisilviculture -combining trees/shrubs and crops, silvopastoral -keeping pasture/animals with trees and agrisilvopastoral -integration of crops, pasture/animals and trees. There is also a temporal agroforestry system called Taungya, which involves the cultivation of forestry tree crops and farmers' subsistence crops on a forest (Hemida et al, 2023).…”
Section: Classification Of Agroforestrymentioning
confidence: 99%